Transformation of the Public Prosecution Service as the Supervisory Authority for Community Service Orders Under the National Criminal Code - Sasqia Putri Ramadhani; Muhammad Azil Maskur (Universitas Negeri Semarang, 2025)
The enactment of Law No. 1 of 2023 (National Criminal Code/KUHP), replacing the colonial-era Criminal Code, marks a significant transformation for the Prosecutor’s Office. The institution must now shift from only executing imprisonment sentences to actively supervising community service punishments in public spaces. The prosecutor’s authority to execute court decisions is reaffirmed in recent regulations, including Article 349 paragraph (2) of Law No. 20 of 2025 on the Criminal Procedure Code (KUHAP). Nevertheless, the lack of comprehensive technical guidelines for the supervisory mechanism continues to pose ongoing challenges. This issue was examined through normative legal research with statutory and comparative approaches to assess the regulatory framework and the prosecutor’s role in executing final and binding (inkracht) court decisions. While a Prosecutor General’s Guideline exists, supervision regulations are broad and lack a specific mechanism for enforcing community service orders. The current system combines community service supervision with conditional punishment and probation, yet still treats community service as a separate category, despite its weaker implementation. The lack of supervision outside working hours increases the risk that offenders may avoid oversight, making the system overly dependent on their good faith.